Gravity compensation design of Delta parallel robots using gear-spring modules. (December 2020) - Nguyen, Vu Linh; Lin, Chyi-Yeu; Kuo, Chin-Hsing
Highlights: A design concept for gravity compensation of Delta parallel robots is presented. Each robot leg installs a geared five-bar mechanism with a compression spring. The FANUC M-3iA/12H Delta robot is adopted for illustrating the design. A comparative study on the designs implemented by the proposed concept, torsional springs, and tension springs are provided. Abstract: This paper presents the gravity compensation for Delta parallel robots by adding a gear-slider mechanism with a compression spring, namely the "gear-spring module, " onto each robot leg. The major significance of the proposing design is that it suggests a compact mechanical solution for gravity compensation of the Delta robot without a compromise of the compensation performance and the robot workspace. The design parameters are determined to approximate the theoretical perfect balancing at a set of targeted configurations. Torque- and energy-reduction criteria are employed to evaluate the performance of gravity compensation. Design examples are implemented through a theoretical design model and a real industrial Delta robot, the FANUC M-3iA/12H. For the theoretical design model, the motor torques of the robot can be effectively reduced within 86 percent of its kinematic workspace. For the industrial Delta robot example, the theoretical peak torque and energy consumption are decreased by up to 38.4% and 55.4% for a pick-and-place task, for which a 10-kgf moving platform is traveling within a range of 1.32 m and a varying speed between 0 and 0.72 m/s. Last, a comparison between the uses of the gear-spring modules, torsion springs, and tension springs for gravity compensation is provided. Graphical abstract: Image, graphical abstract